Incidence of malignancies in patients with juvenile idiopathic arthritis: A retrospective single-center cohort study in Germany. Issue 1 (2nd January 2017) - Barth, Swaantje; Schlichtiger, Jenny; Hartmann, Barbara; Bisdorff, Betty; Michels, Hartmut; Radon, Katja; Hügle, Boris; Walsh, Linda; Haas, Johannes-Peter
Abstract: Objectives : In recent years, concern has been raised about Juvenile Idiopathic Arthritis (JIA) that it could be associated with an increased risk for malignancies. Therefore, the cancer incidence in the JIA patients was evaluated and compared to the cancer incidence in the German population. Methods : A retrospective single-center hospital-based cohort study was performed using data on the JIA patients treated between 1952 and 2010 at the German Center for Pediatric and Adolescent Rheumatology (GCPAR) (Garmisch-Partenkirchen, Germany). Self-administered standardized questionnaires were sent out in 2012. Standardized incidence ratios (SIRs) and their corresponding 95% confidence intervals (95%CIs) were calculated. Results : The study cohort consisted of 3691 JIA patients, and the response rate was 66%. Patients age ranged from 3 to 73 years of which 64% were female. Total follow-up time was 60, 075 person-years; a history of malignancy was reported by 47 patients. Most common types of cancer were melanoma ( n  = 11), cervical cancer ( n  = 8) and breast cancer ( n  = 7). The overall SIR for women was 1.19 (95%CI: 0.77; 1.60) and for men was 0.67 (95%CI: 0.27; 1.07). The SIR for melanoma was 3.21 (95%CI: 1.60; 5.73) in women, whereas in men no melanoma cases were observed. Conclusion : Although no overall increased cancer risk was found, results suggest that the risk of melanoma might be increased in female JIA patients.